Strategic Learning Techniques - Measures Enhancing the Visibility of the Cognitive Process of Learning - Helen Beckmann-Hamzei (Jesuit University Ignatianum in Krakow, 2017)
RESEARCH OBJECTIVE: The aim of the contribution is to provide insights on how strategic learning techniques could constitute measures enhancing the visibility of the cognitive process of learning. THE RESEARCH PROBLEM AND METHODS: The competence of learning as such and its application in practice in educational institutions is a mainly cognitive experience. Copying the learning behavior as such is therefore more difficult compared to the learning through imitation during childhood, as the cognitive part of learning is not immediately visible for the outstanding person wishing to improve his or her learning competence. Alongside three examples from practice, the contribution examines those strategic learning techniques, which can enhance the visibility of the cognitive process of learning. THE PROCESS OF ARGUMENTATION: The pressure of ensuring success at school can lead to the participation of learners in private lessons and revision courses. As participation in these courses mainly focusses on the revision of discipline knowledge that is tested in exams, one may argue that these courses only heal the symptoms of disappointing examination results. RESEARCH RESULTS: The present contribution argues that an investment into the learning competences as such does entail long-term benefits compared to the transferal of discipline knowledge in private lesson and revision courses. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: The drafters of curricula should reassess whether the major focus on discipline knowledge based subjects occupy the majority of curricular obligations is a welcoming development. This development should critically be reflected and perhaps even changed by introducing compulsory strategic learning courses throughout the educational training of learners.